A 10 year retrospective survey of cataract surgery and endophthalmitis in a single eye unit: injectable lenses lower the incidence of endophthalmitis. Issue 7 (1st July 2003) - Mayer, E; Cadman, D; Ewings, P; Twomey, J M; Gray, R H; Claridge, K G; Hakin, K N; Bates, A K
Abstract : Aim: To study the incidence of endophthalmitis following cataract surgery over a 10 year period, and to examine ways in which this may be related to changes in surgical technique. Methods: All cases of endophthalmitis occurring over a 10 year period within a single ophthalmic unit in the United Kingdom were reviewed, and possible risk factors identified. Results: During the study period, as the technique of extracapsular cataract surgery was replaced by phacoemulsification, there was a commensurate reduction in the incidence of endophthalmitis. Injectable IOLs were associated with the lowest risk of postoperative endophthalmitis (0.028%). Conclusions: Injectable intraocular lenses do not make contact with the ocular surface and this may result in the observed lower rate of endophthalmitis. This, and the ease with which they can be inserted through small incisions, support their use as the first line method of lens insertion.